Work in progress – did you check it? : checklist for redesigning a laboratory experiment in engineering education addressing competencies of learning and working 4.0 - Konrad Boettcher and Claudius Terkowsky and Tobias R. Ortelt and Ines Aubel and Sebastian Zug and Marcus Soll and Jan Haase and Bernhard Meussen and Daniel Versick and Matthias Finck and Pierre Helbing and Johannes Nau and Detlef Streitferdt (Lecture notes in networks and systems, 2023)
Due to the possibilities of digitalization, the world of work is undergoing a profound change towards Industry 4.0 and related Learning and Working 4.0. In this context, new competences are expected from employees, which must also be addressed in STEM disciplines, especially in higher engineering education. Lab courses are particularly suitable for this, because here students can actively work on devices and potentially cyber-physical systems. This contribution is the undertaking of a group of lab teachers from various disciplines working on the joint project CrossLab to formulate what they consider the important aspects of lab teaching as learning outcomes for Industry 4.0. Furthermore, as a final goal, they will be transferred into a checklist that can be used in the implementation of existing and newly designed lab experiments with regard to the required competences of Learning and Working 4.0. Constructive Alignment forms the pedagogical framework, in which intended learning outcomes, teaching–learning activities and learning outcome monitoring must be thought through and planned as a whole. The checklist will extend an existing checklist for the thirteen conventional fundamental lab learning-objectives according to Feisel and Rosa. This work in progress describes first results of this attempt.
Keywords: Higher Engineering Education; Industry 4.0; Laboratory Pedagogy